Bringing the Qur'an to life: Teaching students the art of reciting the Qur'an - Farahdiba, Ani Nabila; Haikal, Ahmad Hasanain; Annisa', Raudhatun; Hidayah, Aisyah; Wibowo, Alya Ghina; Riza, Achmad Kemal; Asegaf, M. Maulana (Jurnal Pembelajaran Pemberdayaan Masyarakat (JP2M), 2024)
The majority of Thailand's population is Buddhist. However, there are four provinces in the southern part of Thailand that mostly Muslims inhabit. The UINSA International Community Engagement (UICE) delegation team was assigned to plunge into the Muslim community living in Thailand to revive the Qur'anic values in non-Muslim society. Thus, the Muslim population in Thailand would not lose the Qur'anic values even as a minority. This activity also tries to introduce Qur'an recitation art guidance to Muslims in Southern Thailand who are less familiar with this activity. Therefore, this paper aims to describe the activities of Al-Qur'an reading art education by providing intensive guidance on the recitation of Al-Qur'an as a form of community service. The approach used is a qualitative approach that is Asset Based Community Development that is conducted in five stages, namely initial preparation, analysis, designing expectations, program implementation, and results evaluation. The Qur'an recitation art guidance method involves intensive recitation guidance classes, periodic evaluations, performances, competitions, and presenting prizes. Based on the implementation of these activities, some significant achievements have been obtained to increase the potential of Qur'an recitation art of Attarkiah Islamiah Institute students.